DETERMINANTS OF CUSTOMERS’ ADAPTATION TO INTERNET BANKING: EVIDENCE FROM GREATER JAKARTA AREA, INDONESIA - Nasreen, Jareena; Lubis, Arief Wibisono (UI Scholars Hub, 2021)
Manuscript type: Research Article Research Aims: This paper aims to analyze factors that affect customers’ adaptation to using Internet Banking among banks’ customers in Indonesia. The variables hypothesized to influence adaptation to using Internet Banking are Importance of Internet Banking Needs, Compatibility, Convenience, Communication, and Benefits of Internet Banking. Design/methodology/approach: This study uses Structural Equation Modelling (SEM) on a sample of 215 Internet Banking customers from Greater Jakarta Area, Indonesia. Research Findings: This study found that Benefits of Internet Banking has a significant positive influence on Importance of Internet Banking Needs, which, however, does not influence customer adaptation. Similarly, Compatibility has no influence on customer adaptation. On the other hand, Convenience, and Communication are proven to have significant and positive influences on Customer Adaptation to Internet Banking in Indonesia. Theoretical Contribution/Originality: This research uses the theory of Technology Acceptance Model (TAM) to explain Indonesian customers’ adaptation to Internet Banking by combining the models from Ege Oruç & Tatar (2017) and Jahangir & Parvez (2012).Practitioner/Policy Implication: The results of this study suggest that banks should provide easier, more attractive and secure facilities for users. Banks should invest more in promoting Internet Banking either internally through information by bank officers or spreading media brochures to customers in line at the back. Research limitation/Implications: There are some limitations of this research in terms of the number of respondents, geographical coverage, the model used, questionnaire design and respondent’s perception. Further research might consider to address these issues.